2013
DOI: 10.1080/14697688.2012.745012
|View full text |Cite
|
Sign up to set email alerts
|

Optimal hedging in discrete time

Abstract: Building on the work of Schweizer (1995) andČerný and Kallsen (2007), we present discrete time formulas minimizing the mean square hedging error for multidimensional assets. In particular, we give explicit formulas when a regimeswitching random walk or a GARCH-type process is utilized to model the returns.Monte Carlo simulations are used to compare the optimal and delta hedging methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Furthermore, we state the regime-switching specialization of the optimal hedging algorithm [18] which generates optimal discrete-time (in our case, daily)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we state the regime-switching specialization of the optimal hedging algorithm [18] which generates optimal discrete-time (in our case, daily)…”
Section: Discussionmentioning
confidence: 99%
“…Note that 0 V is chosen such that the expected hedging error G is zero. [18] also showed that t C (defined by…”
Section: T T T T T a E Pmentioning
confidence: 99%
“…Since we fitted a Gaussian HMM to the daily returns, an obvious solution of the hedging problem would be to use the results of [23] for optimal hedging in discrete time; see also [11]. However, implementing this methodology requires interpolating functions on a (d + 1)-dimensional grid.…”
Section: Discrete Time Hedgingmentioning
confidence: 99%
“…Since we fitted a Gaussian HMM to the daily returns, an obvious solution of the hedging problem would be to use the results of Rémillard and Rubenthaler (2013) for optimal hedging in discrete time; see also Rémillard (2013). However, implementing this methodology requires interpolating functions on a (d + 1)-dimensional grid.…”
Section: Discrete Time Hedgingmentioning
confidence: 99%